2005
DOI: 10.1104/pp.104.056549
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Biochemical Characterization of the Selenocysteine Se-Methyltransferase Gene and Se-Methylselenocysteine Synthesis in Broccoli

Abstract: Selenium (Se) plays an indispensable role in human nutrition and has been implicated to have important health benefits, including being a cancer preventative agent. While different forms of Se vary in their anticarcinogenic efficacy, Se-methylselenocysteine (SeMSC) has been demonstrated to be one of the most effective chemopreventative compounds. Broccoli (Brassica oleracea var. italica) is known for its ability to accumulate high levels of Se with the majority of the selenoamino acids in the form of Semethyls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
153
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(167 citation statements)
references
References 57 publications
10
153
3
1
Order By: Relevance
“…6A). When the broccoli plants were treated with 20 mM Na 2 SeO 4 , a concentration imposing no negative effect on broccoli growth (Lyi et al, 2005), a similar expression pattern for BoCOQ5-2 was observed. No significant difference between Se-treated and nontreated samples was observed.…”
Section: Expression Of Bocoq5-2 In Bacteria Resulted In a Dramatic Enmentioning
confidence: 76%
See 2 more Smart Citations
“…6A). When the broccoli plants were treated with 20 mM Na 2 SeO 4 , a concentration imposing no negative effect on broccoli growth (Lyi et al, 2005), a similar expression pattern for BoCOQ5-2 was observed. No significant difference between Se-treated and nontreated samples was observed.…”
Section: Expression Of Bocoq5-2 In Bacteria Resulted In a Dramatic Enmentioning
confidence: 76%
“…To examine whether expression of BoCOQ5-2 increased bacterial tolerance to Se, the growth of the bacterial cells in M9 medium in the presence or absence of 100 mM Na 2 SeO 4 or Na 2 SeO 3 was compared as reported previously (Neuhierl et al, 1999;Lyi et al, 2005). The minimal M9 medium was used for the tolerance assay because bacteria are able to tolerate extremely high concentrations of Se in LB-rich medium.…”
Section: Expression Of Bocoq5-2 In Bacteria Resulted In a Dramatic Enmentioning
confidence: 99%
See 1 more Smart Citation
“…Pickering et al (2003) concluded that SMT gene expression was continuous in tissues of A. bisulcatus. In contrast, Lyi et al (2005) reported that broccoli SMT (BoSMT) expression is up-regulated by selenate treatment. Its expression in leaf has been determined to be involved in development.…”
Section: Discussionmentioning
confidence: 82%
“…In addition of Se hyperaccumulators, in some secondary accumulators such as broccoli (Brassica oleracea var. Italica) (Lyi et al 2005) the accumulation of these non toxic species of Se-amino acids has been suggested to be the basis of Se tolerance (Neuhierl et al 1999). It could be suggested that studied varieties of B. oleracea in this work possess similar mechanism for prevention of Se toxicity.…”
Section: Discussion Dual Effect Of Se On Growthmentioning
confidence: 99%